TEACHING READING COMPREHENSION IN LARGE MULTILINGUAL CLASSROOMS AT THE BASIC EDUCATION LEVEL IN NIGERIA: THE PRESENT SCENARIO - Onyi, Hanna Yusuf (Sokoto Educational Review, 2018)
This paper highlights some of the problems teachers face in teaching reading comprehension in large multilingual classrooms at the basic education level in Nigeria. The paper proposes some strategies that can be used for affective teaching of reading comprehension in large multilingual classrooms. The implication for teachers and the curriculum were highlighted. The paper concludes by suggesting that communicative activities such as role plays question and answer sessions, problem-solving tasks etc. should be incorporated into teachers' lesson plans and teaching. The curriculum for colleges of Education and other teacher training institutions need to be reviewed to provide teachers with the opportunities to competently teach through the medium of at least two languages.